Analisis Potensi Bahaya Lingkungan Kerja Pada Nelayan Tradisional di Wilayah Pesisir - Ella Asri Fauziah; Alif Araafi; Sarda Mauliyand; Abdurrozzaq Hasibuan (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
The largest archipelagic country in Southeast Asia is Indonesia. It is not surprising that the wheels of the Indonesian economy do not only depend on land, but the ocean economy also plays an important role. Fishermen are one of the main jobs in the marine industry. The aim of this literature review is to identify various potential threats to the work environment that traditional fishermen in coastal areas may face. The research results show that physical, chemical, biological, ergonomic and psychosocial factors are the factors that most often arise due to threats to the work environment. Apart from that, unsafe conditions provide a 10% potential for work accidents that occur among fishermen.